2022
DOI: 10.3389/fmicb.2022.999639
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization, and genome sequencing of a novel chitin deacetylase producing Bacillus aryabhattai TCI-16

Abstract: Chitin deacetylase (CDA) is a chitin degradation enzyme that catalyzes the conversion of chitin to chitosan by the deacetylation of N-acetyl-D-glucosamine residues, playing an important role in the high-value utilization of waste chitin. The shells of shrimp and crab are rich in chitin, and mangroves are usually recognized as an active habitat to shrimp and crab. In the present study, a CDA-producing bacterium, strain TCI-16, was isolated and screened from the mangrove soil. Strain TCI-16 was identified and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Therefore, some microorganisms in mangrove sediment may have the function of degrading and utilizing natural chitin during the natural domestication selection process. In our previous study, 22 a CDA-producing bacterium, Bacillus aryabhattai TCI-16 was isolated from mangrove soil. Besides, the complete genome analysis of B. aryabhattai TCI-16 showed that there was a functional gene for encoding CDA, and the primary structure, spatial conformation, amino acid sequence analysis, and phylogenetic analysis indicated that B. aryabhattai TCI-16 CDA (BaCDA) might have a novel structure compared with the CDA proteins from other microorganisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some microorganisms in mangrove sediment may have the function of degrading and utilizing natural chitin during the natural domestication selection process. In our previous study, 22 a CDA-producing bacterium, Bacillus aryabhattai TCI-16 was isolated from mangrove soil. Besides, the complete genome analysis of B. aryabhattai TCI-16 showed that there was a functional gene for encoding CDA, and the primary structure, spatial conformation, amino acid sequence analysis, and phylogenetic analysis indicated that B. aryabhattai TCI-16 CDA (BaCDA) might have a novel structure compared with the CDA proteins from other microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some microorganisms in mangrove sediment may have the function of degrading and utilizing natural chitin during the natural domestication selection process. In our previous study, a CDA-producing bacterium, Bacillus aryabhattai TCI-16 was isolated from mangrove soil. Besides, the complete genome analysis of B.…”
Section: Introductionmentioning
confidence: 99%
“…Chitin deacetylase (CDA) is a metalloenzyme that specifically deacetylates chitin with a green reaction process, stable product quality and uniform acetylation ( Chakraborty et al, 2016 ; Yang et al, 2022 ). The microbial sources of CDAs are narrow, with fungi such as Absidia coerulea, Aspergillus nidulans , and Penicillium oxalicum as the main ones, and bacteria such as Bacillus and Vibrio ( Win and Stevens, 2001 ; Liu et al, 2017 ; Liang et al, 2022 ). Presently, there is no industrial method in existence for generating this enzyme, primarily due to factors including insufficiency of promising microbial varieties and intricate fermentation prerequisites for chitin deacetylase output in numerous reported strains ( Suresh et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%